Over expression of CDK4 and MDM2 in a patient with recurrent ALK-negative mediastinal inflammatory myofibroblastic tumor: A case report. Issue 12 (March 2020) - Hou, Tien-Chi; Wu, Pao-Shu; Huang, Wen-Yu; Yang, Yi-Ting; Tan, Kien Thiam; Liu, Shih-Hua; Chen, Yu-Jen; Chen, Shu-Jen; Su, Ying-Wen
Abstract: Rationale: The diagnosis of anaplastic lymphoma kinase ( ALK )-negative inflammatory myofibroblastic tumors (IMT) remains challenging because of their morphological resemblance with spindle cell sarcoma with myofibroblastic characteristics. Patient concerns: A 69-year-old female patient presented with loco-regional recurrent IMT several times within 8 years after primary treatment and neck lymph node metastasis 3.5 years after last recurrence. Diagnosis: The primary, recurrence, and lymph node metastasis lesions were diagnosed as ALK-negative IMTs based on the histopathological features. Interventions: Biopsy samples were obtained during repeated surgeries and evaluated for genomic alterations during first and recurrent presentations. The evaluation was done using pathway-driven massive parallel sequencing, and genomic alterations between primary and recurrent tumors were compared. Outcomes: Copy number gains and overexpression of mouse double minute 2 homolog ( MDM2 ) and cyclin dependent kinase 4 ( CDK4 ) were observed in the primary lesion, and additional gene amplification of Discoidin Domain Receptor Tyrosine Kinase 2 ( DDR2 ), Succinate Dehydrogenase Complex II subunit C ( SDHC ), and thyroid stimulating hormone receptor ( TSHR ) Q720H were found in the recurrent tumors. Metastases to the neck lymph node were observed 3.5 years after recurrence. Lessons: Our results indicated genetic evolution in a microscopically benign condition and highlighted the importance of molecular characterization of fibro-inflammatory lesions of uncertain malignant potential.